The effect of knowledge management, organizational culture and organizational learning on innovation in automotive industry - Abdi, Kambiz; Mardani, Abbas; Senin, Aslan Amat; Tupenaite, Laura; Naimaviciene, Jurga; Kanapeckiene, Loreta; Kutut, Vladislavas (Journal of Business Economics and Management, 2018)
The main objective of this study was to examine the direct and indirect effects of organizational culture, knowledge management and organizational learning on innovation. The study combined knowledge-based view theory (KBV), competitive value framework to develop a new original theoretical framework for investigation of factors that affect innovation. Data was gathered from a survey of 279 companies supplying automobile parts to Iran Khodro Company, an Iranian leading automobile manufacturer. Study discovered that organizational culture and knowledge management influenced organizational innovation. Besides that, organizational learning played a significant role as a mediator in that relationship. However, knowledge management was not considered as a mediator in the relationship between organizational culture and organizational innovation. As a practical contribution, the findings of the study serve as a guideline for policy makers and managers in the formulation of policies and strategies for sustainable innovation. Knowing the effectiveness of the innovation can help the government to make decisions about the continuation of this policy. Moreover, study contributes to firm management in formulation of policies and strategies for sustainability in innovation context. Innovation assists organizations supplying the product or service in the automotive sector to operate innovatively, competitively and profitably.